Catalytic Oxidative Cleavage of C(OH)-C Bonds in Lignin Model Compounds to Carboxylic Acids by Fe(NO3)3.9H2O/NaI/DMSO - Wang, Xuerong; Sun, Huilin; Li, Caicui; Niu, Shuijiao; Gao, Yu; Chen, Ying; Xu, Tianwei; Wang, Jinhui; Xu, Huanjun (Frontiers in Chemistry, 2022)
The secondary C(OH)-C bonds are abundant in biomass such as lignin and cellulose. Thus, selective cleavage the C(OH)-C bonds into value chemical attracted many attentions. Molecular iodine has received considerable attention as an inexpensive and readily available catalyst to give the corresponding products in excellent yields with high selectivity, but it is highly corrosive and toxic, making its use somewhat unattractive. In this paper, I2 was generated in situ from Fe(NO3)3.9H2O/ NaI, which further combined with Fe(NO3)3.9H2O to catalyze the oxidation process. Aryl primary and secondary benzylic alcohols from the lignin were successfully transformed to aryl carboxylic acids by Fe(NO3)3.9H2O/NaI/DMSO. The catalytic system was green and efficient, avoiding the usage of toxic and corrosive molecular I2. From the experiments, it was clear that electron-donating substituted benzyl alcohols gave higher yields of products than electron-withdrawing substituted substrates, which was similar to the aryl secondary alcohols. Aryl alkyl ketones were also successfully conducted by Fe(NO3)3.9H2O/NaI/DMSO catalytic system.